2018
DOI: 10.1002/polb.24764
|View full text |Cite
|
Sign up to set email alerts
|

Stretching‐induced phase transition of the butene‐1/ethylene random copolymer: Orientation and kinetics

Abstract: The stretching‐induced phase transition from tetragonal Form II to hexagonal Form I and the evolution of corresponding crystallite orientation were studied for the butene‐1/ethylene random copolymer with 1.5 mol % ethylene by using a combination of tensile test and in situ wide‐angle X‐ray diffraction. Three orientation pathways were distinguished for II‐I phase transition, including phase transition accomplishing within off‐axis oriented crystallites (Orientation Pathway 1), phase transition with simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…However, Form I′, described as a defective Form I with lower melting temperature, can be formed through special crystallization procedures, such as solution crystallization, blending with iPP, or copolymerization with other monomers . Actually, quiescent aging at room temperature of Form II samples is generally used for generating trigonal Form I, where the molecular conformation of the chains is that of a 3/1 helix …”
Section: Introductionmentioning
confidence: 99%
“…However, Form I′, described as a defective Form I with lower melting temperature, can be formed through special crystallization procedures, such as solution crystallization, blending with iPP, or copolymerization with other monomers . Actually, quiescent aging at room temperature of Form II samples is generally used for generating trigonal Form I, where the molecular conformation of the chains is that of a 3/1 helix …”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, also for its cross-nucleation behavior, is polybutene-1 (PB-1), which exhibits pronounced polymorphism that can be distinguished by the chain conformation and packing mode of segmental stems . Different helical conformations, that is, the 3/1, 11/3, and 4/1 helixes, can pack into trigonal (form I), tetragonal (form II), and orthorhombic (form III) unit cells. , Among them, the form I unit cell parameters are a = b = 17.5 Å, c (chain axis) = 6.477 Å, and γ = 120° (with space group P 3̅), while form II exhibits a tetragonal unit cell with the parameters a = b = 14.9 Å and c = 21.3 Å (with space group P 4̅ b2 ). The kinetically favored, metastable form II can transform slowly and spontaneously into the stable form I at room temperature. , The transformation is greatly accelerated by the presence of mechanical stresses. , Thanks to the solid-state phase transition, seeds of form I into a PB-1 melt can be created, and form II was demonstrated to cross-nucleate on the surface of such seeds. , Our previous work has revealed that the cross-nucleation efficiency of form II on form I substrates increases with the thickening of form I lamellae, a fact that was interpreted as a possible hint of an epitaxial relationship between the two structures . Therefore, we now aim to further explore and resolve this issue by employing a nanofocused synchrotron X-ray beam on a cross-nucleated PB-1 sample.…”
Section: Introductionmentioning
confidence: 99%
“…39 Of particular interest, also for its cross-nucleation behavior, is polybutene-1 (PB-1), which exhibits pronounced polymorphism that can be distinguished by the chain conformation and packing mode of segmental stems. 40 Different helical conformations, that is, the 3/1, 11/3, and 4/1 helixes, can pack into trigonal (form I), tetragonal (form II), and orthorhombic (form III) unit cells. 41,42 Among them, the form I unit cell parameters are a = b = 17.5 Å, c (chain axis) = 6.477 Å, and γ = 120°(with space group P3̅ ), while form II exhibits a tetragonal unit cell with the parameters a = b = 14.9 Å and c = 21.3 Å (with space group P4̅ b2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the physical means to tune the rate of phase transition [1,21,22,23,24,25,26,27], the chemical regulation of macromolecular structure is another efficient method [28,29,30,31,32]. The molecular structure can be designed by varying molecular weight, as well as regularity, or incorporating the extra structural co-units.…”
Section: Introductionmentioning
confidence: 99%